A proposal for teaching how to formulate and answer critical questions in order to understand argumentative texts / Una propuesta para enseñar a formular y responder preguntas críticas para la comprensión de textos argumentativos. - Pérez, Rocío; Castells, Núria; Minguela, Marta (Culture & Education / Cultura y Educación, 2025)
The access to countless sources and diverse information on the same subject emphasizes the need for sound criteria to compare, analyse and critically assess the vast amount of data available. This article presents an educational programme aimed to teach students how to formulate and use critical questions to assess conflicting information from multiple argumentative news. The programme comprised five sessions and was implemented with third-year secondary school students in their science class. After participating in this programme, students were able to elaborate and to answer critical questions about texts and to identify the quality of the evidence the texts provide. Students valued the educational experience positively, especially the guides they used.